Energy metabolism in obesity: Role of vitamin D status, cold exposure and leucine supplementation - Pathak, Kaveri (Curtin University, 2016)
We studied adaptive thermogenesis, both diet and cold-induced, in the setting of vitamin D status and leucine supplementation. Vitamin D supplementation did not increase fat loss, but higher 25OHD favoured metabolic flexibility. Cold exposure increased thermogenesis only in those with metabolic syndrome. Skin blood flow strongly predicted RMR and RQ. Leucine supplementation had no added effect, over caloric restriction but incidental improvements in 25OHD increased loss of fat mass and retained skeletal muscle mass.